Cross-sectional nanoprobing sample preparation on sub-micron device with fast laser grooving technique. (September 2018) - Tan, P.K.; Zhao, Y.Z.; Rivai, F.; Liu, B.H.; Pan, Y.L.; He, R.; Tan, H.; Mai, Z.H.
Abstract: Cross-sectional sample preparation is one of the most important failure analysis (FA) techniques in the semiconductor industry. It was commonly used for film stack critical dimension measurement, defect identification, electrical fault isolation and etc. However, cross-sectional sample preparation to a specific target location on a sub-micron device is very challenging and time-consuming. This is because of mechanical polishing easily caused metal smear, delamination, film peel-off, micro-cracked and etc. This paper focused on cross-sectional nanoprobing (XNP) sample preparation improvement in quality and quantity. A laser blast to deprocess or create a groove at near to target location before conventional mechanical polishing and focus ion beam (FIB) fine milling. The proposed technique not only reduces the sample preparation time to the sub-micron target location but also prevent mechanical damages that caused by mechanical polishing technique. Highlights: This paper focused on cross-sectional nanoprobing sample preparation to a specific target location on a sub-micron device. A laser blast was used to create a groove at near target location before rough mechanical polishing. The laser blasted groove can prevent mechanical damages when rough mechanical polishing to target location. The laser blasted groove can also shorten the sample preparation time to the sub-micron target location. The experiment and result of the technique were discussed in the paper. The technique was successfully demonstrated and applied to a case study.